Development Of Student’s Activity Sheet (SAS) Based On Problem-Solving About Digestive System Materials In Humans In Class XI SMAN 1 Panyabungan Selatan - Nina Fadilah Lubis; L Lufri (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2021)
The problem behind this research is the way students learn who tend to only read and memorize textbooks. The teaching materials used by schools only rely on textbooks. This study aims to produce SAS based on problem-solving in the digestive system material in humans that is valid and practical. The SAS was validated by lecturers in the biology department of FMIPA UNP and biology teacher at SMAN 1 Panyabungan Selatan. The practicality of this product was carried out by one biology teacher and fifty students at SMAN 1 Panyabungan Selatan. As a result, problem-solving-based worksheets were developed using 3 stages of the 4D model, namely the define stage by analyzing learning needs using the curriculum, the design stage by Designing SAS components, and the Develop stage which aims to produce valid and practical SAS. The value of validity is 92.02% with very valid criteria, practicality by teachers is 90.38% with the criteria is very feasible and students are 89.28% with very feasible criteria. Based on this study, it can be concluded that Student Activity Sheets (SAS) based on problem-solving have been produced on the material of digestive system in humans in class XI of SMAN 1 Panyabungan Selatan which are valid and practical.